iOS Technologies & Frameworks - Vitale, Nino Santos (2016)
Apple’s mobile platform — iOS — currently generates the largest amount of revenue out of all mobile app stores. The majority of iDevices run the latest major iOS version (iOS 10) due to Apple users’ tendency to update their devices. Consequently, iOS developers are pressured into keeping their apps up to date. Advantages to updating apps consist of new features and adapting apps to the platform’s hardware and software evolution. However, this does not always happen. There are apps, some popular (with many users), which either receive slow updates, or not at all. The main consequence of developers not updating to the latest tendencies (i.e. user interface or API changes) is the degradation of their apps’ user experience. This subpar user experience leads to a decrease in the number of installs (and sales) and a search for alternatives that have been updated to support the latest firmware iteration fully. We identified a common pattern amongst ten apps which have subpar reviews on the App Store: excessive battery consumption and lack of user onboarding were just a few of the ssues. Above all, almost all those apps belong to the top 1% of apps (which generate 94% of the App Store’s revenue), so the lack of focus on the user experience is unfortunate considering their massive user bases. We listed the available resources for those wanting to develop or improve iOS apps. Given these requisites, we studied the possibility of developing a mobile app that adopted good engineering practices and, above all, focused on delivering an excellent user experience in a given timeframe of six months. The app’s idea consisted of a wish list management app called Snapwish that allows the user to take photos of objects they want, create wish lists, and share them with family and friends. The app allows for offline usage, with data syncing automatically (in real-time) without user intervention when the app’s Internet connection is present. We tested Snapwish thoroughly to measure the quality of its implementation. Profiling helped assert that core metrics like CPU and memory usage, network data requests and energy consumption were within acceptable values while unit and user interface tests served to validate our code functionally. Furthermore, our team of five beta testers provided valuable feedback and suggestions. Ultimately, the six-month timeframe proved to be insufficient in regards to a release on the App Store, as Snapwish remains in the latter beta stages at the time of writing. This delay is mostly attributed to a lengthy testing process. Thus, we plan on releasing it in the first trimester of 2017.